PENGARUH DEBT TO EQUITY RATIO, RETURN ON ASSET DAN INFLASI TERHADAP HARGA SAHAM PT. ASTRA OTOPARTS, TBK - Betari Anisa; Sunartiyo (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The share price is the price set by a company against the letter of share ownership in the company. Many factors can affect the stock price, namely the company's internal factors and the company's external factors. There are many internal factors of the company that can affect the stock price, but in this study the author conducted a study on the variables Debt to equity ratio and return on asset to the share price of PT. Astra Otoparts. In addition, the external factor of the company that the author will study is inflation. The method used in this study is a multiple linear regression analysis. This study used secondary data using the purposive sampling method. The results of hypothesis testing show that DER partially has a positive and significant influence on the share price of PT. Astra Otoparts, Tbk; ROA partially has a positive and significant influence on the share price of PT. Astra Otoparts, Tbk, and Inflation partially have a positive and significant influence on the share price of PT. Astra Otoparts, Tbk. DER, ROA, and Inflation simultaneously have a positive and significant influence on the share price of PT. Astra Otoparts.